2014
DOI: 10.1039/c3cc47225f
|View full text |Cite
|
Sign up to set email alerts
|

A ratiometric and colorimetric luminescent thermometer over a wide temperature range based on a lanthanide coordination polymer

Abstract: A lanthanide coordination polymer Tb0.957Eu0.043cpda was synthesized as a ratiometric and colorimetric luminescent thermometer. The high triplet excited state energy of a linker enables Tb0.957Eu0.043cpda to detect and visualize temperature over a wide range from cryogenic to room temperature (40-300 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(92 citation statements)
references
References 28 publications
0
92
0
Order By: Relevance
“…Compared with [Tb 0.957 Eu 0.043 (H 2 cpda)(Hcpda)(H 2 O)] ⋅ 6 H 2 O (H 3 cpda: 5‐(4‐carboxyphenyl)‐2,6‐pyridinedicarboxylic acid) with adjustable photoluminescence reported by Cui et al,23 the formula [(Eu x Tb 1− x )(IN) 2 L] reported in this paper can readily generate tunable photoluminescence properties by changing Eu III /Tb III ratios. In addition, because Eu 3+ and Tb 3+ within the sample emit different colors of red at 612 nm and green at 545 nm, respectively, the luminescence colors of [(Eu x Tb 1− x )(IN) 2 L] can also readily generate tunable colors from red to yellow, and green.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with [Tb 0.957 Eu 0.043 (H 2 cpda)(Hcpda)(H 2 O)] ⋅ 6 H 2 O (H 3 cpda: 5‐(4‐carboxyphenyl)‐2,6‐pyridinedicarboxylic acid) with adjustable photoluminescence reported by Cui et al,23 the formula [(Eu x Tb 1− x )(IN) 2 L] reported in this paper can readily generate tunable photoluminescence properties by changing Eu III /Tb III ratios. In addition, because Eu 3+ and Tb 3+ within the sample emit different colors of red at 612 nm and green at 545 nm, respectively, the luminescence colors of [(Eu x Tb 1− x )(IN) 2 L] can also readily generate tunable colors from red to yellow, and green.…”
Section: Resultsmentioning
confidence: 97%
“…The temperature‐dependence of the emission spectrum of compounds 8 – 10 are investigated at 77 and 293 K in Figure 9. The luminescent intensity of both Tb 3+ and Eu 3+ in 8 and 9 increases as the temperature increases, which is due to the thermal activation of nonradiative‐decay pathways 23. Interestingly, compound 10 exhibits a significantly different luminescent behavior compared to those of 8 and 9 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, two other Eu 3+ /Tb 3+ mixed MOF Tb 0.9 Eu 0.1 PIA (H 2 PIA = 5-(pyridin-4-yl)isophthalic acid) 66 and Tb 0.957 Eu 0.043 cpda (H 3 cpda = 5-(4-carboxyphenyl)-2,6-pyridinedicarboxylic acid) were designed and prepared using the ligand with higher triplet excited energies. 67 The response range of Tb 0.9 Eu 0.1 PIA is from 100 to 300 K, and that of Tb 0.957 Eu 0.043 cpda is from 40 to 300 K. Both of them display the maximum relative sensitivity at 300 K, and they are 3.27%K -1 and 16.03%K…”
Section: Sensing Of Temperaturementioning
confidence: 95%
“…Qian, Chen, and co‐workers have designed and developed a series of ratiometric luminescent temperature sensors and elaborated the concept of thermometry . The dual‐emission LnMOF temperature sensors can be divided into two modes: 1) Mixed‐lanthanide dual‐emission MOF, most reported temperature sensors belong to this type, but its shortcoming is that the emission peak is relatively fixed, so it cannot be adjusted and expanded and 2) upon encapsulating fluorescent dye guest into a luminescent LnMOF host (dye⊂LnMOF), by choosing different kinds of fluorescent guests, not only the luminescent range can be extended, but also the luminescent properties can be adjusted by the interaction between different fluorescent guests and LnMOF hosts . However, this method is not blind encapsulation, but should fully consider the size effect and functionalized pore interaction between dyes and MOFs .…”
Section: Figurementioning
confidence: 99%